Designing Cartoon as a Supplementary English Material for English Structure Subject - Putranti, Sulistini Dwi; Mina, Nurawati (IAIN Samarinda, 2015)
Cartoon comes from an Italian word ‘Cartone’ meaning a large paper. It is designed not only as the media to describe daily activities, but also to entertain, criticize, provoke, and even to teach people. A lot of studies have been conducted regarding the implementation of cartoon in classroom or outside classroom context. It is proven that cartoon gives some positive attitudes in teaching students. However, the knowledge in how to design and utilize the cartoon based on teachers’ and/or students’ needs should be revealed. This article allows teachers and students to know the process and the basic principles of how a cartoon for learning is designed in the context of English Structure class. The method used in this study is design and development research. The result of this study is a cartoon entitled The Tragedy of Jayaprana which promotes the narrative text as the topic of the learning.